Fé na mídia: um estudo das imagens técnicas (TV Record) como estratégia de comunicação e sobrevivência da Igreja Universal do Reino de Deus - Fonteles, Heinrich (2012)
This research had the objective to study the power of media image and its constitution of the locus of faith, articulated to journalistic language, which is considered in a neutral, rationalized and objective way.This is a theorical study which used an interdisciplinary methodological approach based on the culturalist theory, articulated to: (a) theories of image and media, seeking to identify the origins of visual image, in order to review how it is evoked in the context of a semiotic media communication environment, and (b) sociological, religious and political theories, in order to discuss power, modernity and neo religiosity. In order to do that, it was chosen the journalistic TV program Jornal da Record (JR) as the object of analysis, which presents the closeness and distance between religion and communication, seen in JR´s defense reports related to the scandals of the Universal Church of the Kingdom of God (UCKG), that occurred in 2009. The theoretical bases for this study were Pross concepts of media, Flusser s concepts of scalable image technique abstraction, Baitello Jr. s concepts of pure iconophagy, and the ideas proposed by the imaginaries and mediosphere criticism to the paradigm of modernity and Contrera´s disenchantment of the world. The survey´s results indicate that faith in the media is possible, since it brings evidence of reality to a person. The neo religions, originated in this array, put their trust in the media as a way to publicize their ideas, since images bring possibilities and intensify the impact on society through the notion of concepts and possible simulation-hypotheses that can be put into practice. Reality, therefore, is considered as religious points of view, disguised through rationality. It is important to note that notions of imagery concepts exempt persons from interpreting reality, as other spheres of mediations produce possible facts and hypotheses when supported on iconophagy (pure) as a way to trick the collective memory of events, because the resource to previous images can be highly manipulatable. Therefore, the UCKG, through TV Record s journalism, found a way to work in both fields at once: reality and religion. Their stories began to represent the raw material of religious TV programs, both with popular roots, thus, becoming anegotiable economic value . This way, the sustained UCKG s speech in the media affects and influences popular imagination